Borderland City in New India - McDuie-Ra, Duncan (Asian Borderlands, 2016)
Borderland Cities in New India explores contemporary urban life in two cities in India's Northeast borderland at a time of dramatic change. Social and economic transformation from India's embrace of neoliberalism and globalisation, often referred to as 'new' India, has become a popular subject for academic analysis in the last decade. This is epitomised by focus on so-called 'mega-cities', reflecting a general trend in scholarship on other parts of Asia. However, far less attention has been afforded to borderland regions and to the provincial cities of 'new' India. Using ethnographic material, this book focuses on two cities in India's Northeast borderland: Aizawl and Imphal. Both cities have been profoundly affected by armed conflict, militarism, displacement, and inter-ethnic tensions. Yet, both are also experiencing intensified flows of goods and people, rapid urban development, and expansion of Indian and foreign capital associated with the opening of the borderland west to the rest of India and east to the rest of Asia. This title was made Open Access by libraries from around the world through Knowledge Unlatched.